PTH-014 Bowel scope screening programme; depth of insertion and withdrawal times vs adenoma detection rate. (22nd June 2015) - Warburton, R; Meagher, U; Field, A; Tighe, R
Abstract : Introduction: The Norwich bowel cancer screening centre was one of the initial pilot sites for launch of the Bowel scope screening programme commencing in May 2014. One key performance indicator of Bowel scope screening programme is the adenoma detection rate (ADR), and concern has been expressed that low ADRs reflect missed adenomas and therefore may reduce the beneficial effect of the programme. Nationally, there has been variation in adenoma detection rates between both individual endoscopists and the pilot screening centres. Speculation has been made that the depth of insertion of the endoscope may negatively correlate with ADR, possibly as less time is available for close inspection of the colonic mucosa on withdrawal. Method: We have analysed data on BCSS from the last 18 months derived from the Norwich screening centre. A total of 11 endoscopists have performed more than 50 bowel scope procedures each, totalling 4824 over the 18 months with an ADR of 9.14%. The procedures were stratified by depth of insertion and examined for ADR and withdrawal times. Results: Passage of the endoscope to the splenic flexure was associated with a higher ADR compared with passage to the sigmoid colon (9.94% Splenic Flexure; 9.09% Transverse Colon; 5.49% Sigmoid Colon) (X 2 4.72; p = 0.03). Passage of the endoscope only to the rectum was associated with a very high ADR (32.14%) – presumably because the procedure was stopped because a large polyp was identified (Table 1 ). Passage of the endoscope to the splenic flexure was associated with a longer withdrawal time compared with passage to the sigmoid colon (3.4 min for Splenic Flexure; 3.6 min for Transverse Colon and 2.1 min for Sigmoid Colon). The data for individual endoscopists was also analysed by percentage passage of the endoscope to the splenic flexure, individuals' ADR and individuals' withdrawal times. There was no correlation between the ADR and either percentage passage to the splenic flexure or the individuals' overall withdrawal times. Conclusion: The depth of insertion of the endoscope correlates positively with higher ADR, and is not associated with shorter withdrawal times. It is likely that individual lesion recognition skills of the endoscopist are responsible for the variations in ADR seen within Bowel Scope. Disclosure of interest: None Declared.